Racial Differences in Left Ventricular Mass and Wave Reflection Intensity in Children - Heffernan, Kevin S.; Lefferts, Wesley K.; Atallah-Yunes, Nader H.; Glasgow, Alaina C.; Gump, Brooks. B. (Frontiers in Pediatrics, 2020)
The burden of heart failure is disproportionately higher in African Americans (AAs), with a higher prevalence seen at an early age. Examination of racial differences in left ventricular mass (LVM) in childhood may offer insight into risk for cardiac target organ damage (cTOD) in adulthood. Central hemodynamic load, a harbinger of cTOD in adults, is higher in AAs. The purpose of this study was to examine racial differences in central hemodynamic load and LVM in AA and non-Hispanic white (NHW) children. 269 children participated in this study (age, 10±1 years; n = 149 female, n = 154 AA). Carotid pulse wave velocity (PWV), forward wave intensity (W1) and reflected wave intensity (negative area, NA) was assessed from simultaneously acquired distension and flow velocity waveforms using wave intensity analysis (WIA). Wave reflection magnitude was calculated as NA/W1. LVM was assessed using standard 2D echocardiography and indexed to height as LVM/[(height(2.16)) + 0.09]. A cutoff of 45g/m(2.16) was used to define left ventricular hypertrophy (LVH). LVM was higher in AA vs NHW children (39.2±8.0 vs 37.2±6.7 g/m(2.16), adjusted for age, sex, carotid systolic pressure and socioeconomic status; p <0.05). The proportion of LVH was higher in AA vs NHW children (25 vs 12 %, p <0.05). AA and NHW children did not differ in carotid PWV (3.5±4.9 vs 3.3±1.3 m/s; p >0.05). NA/W1 was higher in AA vs NHW children (8.5±5.3 vs 6.7±2.9; p < 0.05). Adjusting for NA/W1 attenuated racial differences in LVM (38.8±8.0 vs 37.6±7.0 g/m(2.16); p = 0.19). In conclusion, racial differences in central hemodynamic load and cTOD are present in childhood. AA children have greater wave intensity from reflected waves and higher LVMI compared to NHW children. WIA offers novel insight into early life origins of racial differences in central hemodynamic load and cTOD.